Optimisation of the Colour Analysis of Microwave Dried Tomato Applying Taguchi Technique: Colour Analysis of Microwave Dried Tomato - Hussein, Jelili; Oke, Moruf Olanrewaju; Adeyanju, James Abiodun; Abiona, Oluseye Oladapo (Journal of Agricultural Sciences (Belgrade), 2022)
The changes in the colour of dried tomatoes affect their acceptability. Digital imaging with Photoshop software and optimisation with Taguchi technique was explored to determine the surface colour of microwave dried tomato slices. The tomatoes sample was pretreated with water blanching (WB), ascorbic acid (AA) and sodium metabisulphite (SB). Cut into 4 mm, 6 mm and 8 mm thickness and dried at 90W, 180W and 360W microwave power level following Taguchi experimental design. Colour characteristics (L*, a*, b*, change in colour, browning index, hue, and chroma) of the dried tomato slices were determined. The L*, a*, and b* values of fresh tomato were 56.73, 44.51, and 38.38. The optimum processing conditions for the colour characteristics varied significantly (p< 0.05). Pretreatment is the prime significant processing parameter controlling the L*, b*, ΔE, BI, and hue values. At the same time, the slice thickness had a considerable influence on the a*, ratio of a*/b* and chroma values.